Reversible biomechano-responsive surface based on green fluorescent protein genetically modified with unnatural amino acids. Issue 1 (12th November 2014) - Longo, Johan; Yao, Chunyan; Rios, César; Chau, Nguyet Trang Thanh; Boulmedais, Fouzia; Hemmerlé, Joseph; Lavalle, Philippe; Schiller, Stefan M.; Schaaf, Pierre; Jierry, Loïc
Abstract : Uniaxial stretching of modified GFP "clicked" onto an elastomer leads to a repeatable and reversible decrease of its fluorescence intensity. Abstract : GFP has been genetically modified at two specific positions of its molecular architecture. These modifications allow its covalent attachment onto PEG brushes grafted on functionalized silicone surfaces. The stretching of this material leads to a reversible decrease of the fluorescence intensity due to stretch-induced forces applying on GFP molecules.